BREAKING THE GENERATION THEORY OF HUMAN RIGHTS: Mapping the Scope of Justiciability of Economic, Social and Cultural Rights with Special Reference to the Constitutional Guarantees in Nepal - Sangroula, Geeta Pathak (Kathmandu School of Law Review, 2013)
‘Though the human rights can be classified in accordance with their nature however, in essence, it is not reasonable to think as co placement and irresponsibility, that by making the essence of human rights secondary; by making one immediately useable and the other opposite to it.